2022
DOI: 10.1111/jocs.16209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tricuspid valve thrombosis: A midterm follow‐up study

Abstract: Background: The incidence of prosthetic tricuspid valve (TV) thrombosis is the highest among heart valves. It can lead to high morbidity and mortality without proper treatment. In this study, we sought to report the management and clinical outcomes of patients with mechanical TV thrombosis.Methods: The current study was conducted in Rajaei Heart Center on 42 patients with mechanical TV thrombosis from 2006 to 2017. The baseline characteristics and the rates of adverse events during the follow-up period were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another study compared five thrombolytic regimens for treating prosthetic valve thrombosis, including ten cases of the mechanical tricuspid valve, reported that ultra‐slow infusion of alteplase (25 mg over 25 h) had an overall success rate of 85% and the lowest complication rate compared to the other regimens. There have been no reported complications in patients with the heart valve in tricuspid position 19 . There are a few published articles describing the use of fibrinolysis in bioprosthetic valves, and we found only one case report of thrombolytic therapy for THV thrombosis.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Another study compared five thrombolytic regimens for treating prosthetic valve thrombosis, including ten cases of the mechanical tricuspid valve, reported that ultra‐slow infusion of alteplase (25 mg over 25 h) had an overall success rate of 85% and the lowest complication rate compared to the other regimens. There have been no reported complications in patients with the heart valve in tricuspid position 19 . There are a few published articles describing the use of fibrinolysis in bioprosthetic valves, and we found only one case report of thrombolytic therapy for THV thrombosis.…”
Section: Discussionmentioning
confidence: 79%
“…There have been no reported complications in patients with the heart valve in tricuspid position . 19 There are a few published articles describing the use of fibrinolysis in bioprosthetic valves, and we found only one case report of thrombolytic therapy for THV thrombosis. Akhras et al reported a case of transcatheter mitral valve thrombosis early after the procedure and significant improvement of gradients and systolic pulmonary artery pressure 8 h after alteplase infusion at a rate of 10 mg/h.…”
Section: Case Presentationmentioning
confidence: 85%
See 2 more Smart Citations
“…To the Editor, I congratulate Shojaeifard et al 1 for their successful management of mechanical tricuspid valve thrombosis. Cardiac surgery nowadays is rapidly changing and at a crucial turning point.…”
Section: Impact Of Percutaneous Valve Intervention On Mechanical Valv...mentioning
confidence: 99%